2020
DOI: 10.1007/jhep10(2020)080
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Goldstone dark matter: gravitational waves and direct-detection blind spots

Abstract: Pseudo-Goldstone dark matter is a thermal relic with momentum-suppressed direct-detection cross section. We study the most general model of pseudo-Goldstone dark matter arising from the complex-singlet extension of the Standard Model. The new U(1) symmetry of the model is explicitly broken down to a CP-like symmetry stabilising dark matter. We study the interplay of direct-detection constraints with the strength of cosmic phase transitions and possible gravitational-wave signals. While large U(1)-breaking inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 74 publications
1
35
0
Order By: Relevance
“…We also remark that one can accommodate a variant of this scenario in which the DM is a pseudo-Goldstone boson of the aforementioned global U( 1) symmetry [64][65][66]. Despite of its interesting phenomenology, especially for what concerns DM direct detection [67][68][69][70], we will not consider this scenario here.…”
Section: Scalar Dark Mattermentioning
confidence: 99%
“…We also remark that one can accommodate a variant of this scenario in which the DM is a pseudo-Goldstone boson of the aforementioned global U( 1) symmetry [64][65][66]. Despite of its interesting phenomenology, especially for what concerns DM direct detection [67][68][69][70], we will not consider this scenario here.…”
Section: Scalar Dark Mattermentioning
confidence: 99%
“…Nevertheless, a study [12] showed that such phase transitions can only be of second order and impossible to produce stochastic GWs. Further studies tried to introduce extra terms to break the U(1) symmetry, e.g., the soft cubic terms [36], or the most general breaking terms [45]. These efforts successfully achieved first-order phase transitions (FOPTs) and stochastic GWs, but the essential merit of the vanishing tree-level DM-nucleon scattering in the zero momentum transfer limit is sacrificed.…”
Section: Jhep05(2021)160mentioning
confidence: 99%
“…Many Higgs portal models have a second scalar that mixes with the Standard Model (SM) Higgs boson [7,9,10,12,14,17,[20][21][22][23]25,26,38,54,[58][59][60][61][62][63][64]. The mechanism leading to blind spots in such models is the destructive interference between the Higgs-like scalar and the second scalar in the direct detection cross section amplitude [9,10,12,17,20,21,23,26,54,61,63]. Given that detecting dark matter is the focus of a broad experimental program, we felt it useful to further explore regions of the parameter space that give rise to suppressed direct detection cross sections.…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, many possible variations of this simple picture that can give rise to cancellations in the direct detection cross section. An incomplete list of possibilities appearing in the literature consists of the scalar portal being replaced with a pseudoscalar portal [22,55,[65][66][67][68][69][70][71][72], or having a complex scalar which gives rise to a second scalar portal [20,26,26,57,73,74], a two Higgs doublet model [22,23,55,63,64,[69][70][71][74][75][76][77], higher Higgs representations [78], or supersymmetric models [22,52,54,[79][80][81][82]. Before proceeding, we note that, given that we simply want to push the simplest of models as far as we could, we haven't dealt with the issue of UV completeness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation